Improved treatment of dark matter capture in neutron stars III: nucleon and exotic targets. Issue 11 (29th November 2021) - Anzuini, Filippo; Bell, Nicole F.; Busoni, Giorgio; Motta, Theo F.; Robles, Sandra; Thomas, Anthony W.; Virgato, Michael
Abstract: We consider the capture of dark matter (DM) in neutron stars via scattering on hadronic targets, including neutrons, protons and hyperons. We extend previous analyses by including momentum dependent form factors, which account for hadronic structure, and incorporating the effect of baryon strong interactions in the dense neutron star interior, rather than modelling the baryons as a free Fermi gas. The combination of these effects suppresses the DM capture rate over a wide mass range, thus increasing the cross section for which the capture rate saturates the geometric limit. In addition, variation in the capture rate associated with the choice of neutron star equation of state is reduced. For proton targets, the use of the interacting baryon approach to obtain the correct Fermi energy is essential for an accurate evaluation of the capture rate in the Pauli-blocked regime. For heavy neutron stars, which are expected to contain exotic matter, we identify cases where DM scattering on hyperons contributes significantly to the total capture rate. Despite smaller neutron star capture rates, compared to existing analyses, we find that the projected DM-nucleon scattering sensitivity greatly exceeds that of nuclear recoil experiments for a wide DM mass range.